Crack filling in concrete by addition of Bacillus subtilis spores – Preliminary study (2018)
This study aimed to analyze the performance of two concrete mixtures with the addition of B. subtilis spores regarding their capacity of filling cracks during the curing time, evaluating whether the addition can influence the compressive strength of the concrete. For so, six concrete mixtures were studied divided in two mix compositions: 1:1:2 and 1:2:3 (cement: sand: gravel) with w/c of 0.33 and 0.45, respectively. For each composition were added concentrations of 0, 0.3x108 or 1.2x108 of B. subtilis spores/mL. The results showed that all the samples with spores addition presented crystals precipitation, possibly calcium carbonate, that visually filled the cracks. However, more studies of microstructural analysis should be conducted to prove that the cracks were closed. The compressive strength presented satisfactory results, because the addition of 1.2x108 spores/mL did not present significant differences in compressive strength at probability level of 5%, when compared to the reference concrete.